Sula Islands Regency, North Maluku Province; Financial Independence Study - Abdul Hadi Sirat; Nurlaila Latupono; Milwan Milwan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to determine and analyze the regional financial independence of the Sula Islands Regency, North Maluku Province in order to support the implementation of regional development as the implementation of a decentralized system (local government), the contribution of local revenue (PAD) to the APBD of the Sula Islands Regency in 2017-2021. Research informant is Head of Regional Tax and Levy Management Agency. The results show that the ratio of regional financial independence in the Sula Islands Regency is still low or is in a consultative relationship pattern. Effectiveness Ratio and Efficiency Ratio which shows the highly efficient regional financial capacity. The compatibility ratio shows that the results of operational expenditures are greater than capital/development expenditures. Meanwhile, the growth ratio overall experienced positive and negative growth. The contribution of PAD to the APBD of the Sula Islands Regency is still low or lacking. Lack of local government commitment, both executive and legislative, in increasing PAD which affects the amount of increasing regional financial independence, lack of loyalty from both executives and legislatures in managing regional finances from the planning to implementation sector, and lack of local government innovation in exploring the potentials of the Islands Regency. Sula to increase regional financial independence